Mechanism Design Theory in Control Engineering: A Tutorial and Overview of Applications in Communication, Power Grid, Transportation, and Security Systems - Chremos, Ioannis Vasileios; Malikopoulos, Andreas A. (IEEE control systems, 2024)
This article provides an introduction to the theory of mechanism design and its application to engineering problems. Our aim is to provide the fundamental principles of mechanism design for control engineers and theorists, along with state-of-the-art methods in engineering applications. We start our exposition with a brief overview of game theory, highlighting the fundamental notions necessary to introduce mechanism design. Then, we offer a comprehensive discussion of the principles of mechanism design. Finally, we explore four key applications in engineering, that is, communication networks, power grids, transportation, and security systems.